(untitled) (Research, Society and Development, 2024)
This article focuses on rural settlements in Brazil. It aims to analyze the models of rural settlements, according to data from the National Institute for Colonization and Agrarian Reform. It questions the implications of the country’s agrarian policies for the settlers. Its hypothesis is that the organization of settlements should be based on the implementation of collective practices that promote the union, strengthening and social development of the group. The methodology used in this study was qualitative, reflective with a theoretical-social and exploratory focus, focusing on regional development, public policies and work. It relied on secondary sources. In order to systematize the data, the research was divided into three stages: pre-analysis of the data; study of the material; subsequent treatment of the results, inference and interpretation. It uses the science of history as a method for grasping facts in their entirety, based on the contradiction between productive forces and relations of production. The results show that in the collective organization model, once settled, the families fight and work together to achieve diversified food production, restore the balance of the environment, as well as the restitution and protection of the social and economic rights of all rural workers. He concludes that this collective organization, while enabling the resolution of internal problems, builds effective responses to external challenges.